Strong conservation of inbred mouse strain microRNA loci but broad variation in brain microRNAs due to RNA editing and isomiR expression - Trontti, Kalevi (RNA, 2018)
Diversity in the structure and expression of microRNAs, important regulators of gene expression, arises from SNPs, duplications followed by divergence, production of isomiRs, and RNA editing. Inbred mouse strains and crosses using them are important reference populations for genetic mapping, and as models of human disease. We determined the nature and extent of interstrain miRNA variation by (i) identifying miRNA SNPs in whole-genome sequence data from 36 strains, and (ii) examining miRNA editing and expression in hippocampus (Hpc) and frontal cortex (FCx) of six strains, to facilitate the study of miRNAs in neurobehavioral phenotypes. miRNA loci were strongly conserved among the 36 strains, but even the highly conserved seed region contained 16 SNPs. In contrast, we identified RNA editing in 58.9% of miRNAs, including 11 consistent editing events in the seed region. We confirmed the functional significance of three conserved edits in the miR-379/410 cluster, demonstrating that edited miRNAs gained novel target mRNAs not recognized by the unedited miRNAs. We found significant interstrain differences in miRNA and isomiR expression: Of 779 miRNAs expressed in Hpc and 719 in FCx, 262 were differentially expressed (190 in Hpc, 126 in FCx, 54 in both). We also identified 32 novel miRNA candidates using miRNA prediction tools. Our studies provide the first comprehensive analysis of SNP, isomiR, and RNA editing variation in miRNA loci across inbred mouse strains, and a detailed catalog of expressed miRNAs in Hpc and FCx in six commonly used strains. These findings will facilitate the molecular analysis of neurological and behavioral phenotypes in this model organism.